Accumulated workloads and the acute:chronic workload ratio relate to injury risk in elite youth football players - Bowen, L.; Gross, A. S.; Gimpel, M.; Li, F. X. (British Journal of Sports Medicine, 2017)
Aim: The purpose of this study was to investigate the relationship between physical workload and injury risk in elite youth football players.